Reversible Switching of the Dirac Point in Graphene Field-Effect Transistors Functionalized with Responsive Polymer Brushes - Piccinini, Esteban (2019)
The reversible control of the graphene Dirac point using external chemical stimuli is of major interest in the development of advanced electronic devices such as sensors and smart logic gates. Here, we report the coupling of chemoresponsive polymer brushes to reduced graphene oxide (rGO)-based field-effect transistors to modulate the graphene Dirac point in the presence of specific divalent cations. Poly[2-(methacryloyloxy)ethyl] phosphate (PMEP) brushes were grown on the transistor channel by atom transfer radical polymerization initiated from amine-pyrene linkers noncovalently attached to rGO surfaces. Our results show an increase in the Dirac point voltage due to electrostatic gating effects upon the specific binding of Ca2+ and Mg2+ to the PMEP brushes. We demonstrate that the electrostatic gating is reversibly controlled by the charge density of the polymer brushes, which depends on the divalent cation concentration. Moreover, a theoretical formalism based on the Grahame equation and a Langmuir-type binding isotherm is presented to obtain the PMEP–cation association constant from the experimental data.